Non-isothermal, Multi-phase, Multi-component Flows through Deformable Methane Hydrate Reservoirs. - Gupta, Shubhangi (Technical University of Munich, 2016)
We present a multiphysics model and numerical solution framework for subsurface methane hydrate systems. The model development focusses on natural gas production through depressurization and thermal stimulation methods. The model considers kinetic hydrate phase change and non-isothermal, multi-phase, multi-component flow in linear-elastically deforming soils, and accounts for the dynamic effects on the mechanical and the fluid-solid interaction properties occurring due to the chemo-hydro-geo-mechanical coupling. We develop numerical solution strategies for this model and validate against several benchmark tests, analytical solutions, and experimental data. Wir präsentieren ein Multiphysik-Modell und eine numerische Lösungsmethode für unterirdische Methanhydrat Systeme. Der Fokus des Modells liegt auf Erdgasförderung durch Reduktion des Druck oder thermische Stimuation. Das Modell berücksichtigt kinetische Phasenänderung des Hydrats und nicht-isotherme Mehrphasen-Mehrkomponenten-Strömung in linearelastisch verformbaren Böden. Die dynamischen Auswirkungen der chemo-hydro-geo-mechanische Kopplung auf die mechanischen und hydraulischen Eigenschaften des Hydrats werden ebenso mit einbezogen. Wir entwickeln numerische Lösungsstrategien für dieses Modell, und validieren diese gegen verschiedene Standardtests, analytische Lösungen, und experimentell ermittelte Messungen.